2014
DOI: 10.1055/s-0034-1387951
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectroscopy in the Diagnosis of Ulcerative Colitis

Abstract: Raman spectroscopy can distinguish UC from normal colon tissue rapidly and accurately. This technology offers the possibility of real-time diagnosis as well as the ability to study changes in UC-afflicted colon tissue that do not appear histologically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…In one of the first studies published on the topic, using colorectal biopsy specimens from 8 patients who underwent surgery, Veenstra et al [8] managed to differentiate subjects with UC from healthy subjects with a sensitivity of 82% and a specificity of 89%, with significant differences in the spectral regions associated with nucleic acids (1,044 cm -1 ), lipids (1,102 and 1,656-1,658 cm -1 ) and proteins (755, 1,030-1,032, 1,102, 1,170-1,173, 1,246, 1,613 and 1,656-1,658 cm -1 ), explained by the development of inflammation and increased cell turnover.…”
Section: Discussionmentioning
confidence: 99%
“…In one of the first studies published on the topic, using colorectal biopsy specimens from 8 patients who underwent surgery, Veenstra et al [8] managed to differentiate subjects with UC from healthy subjects with a sensitivity of 82% and a specificity of 89%, with significant differences in the spectral regions associated with nucleic acids (1,044 cm -1 ), lipids (1,102 and 1,656-1,658 cm -1 ) and proteins (755, 1,030-1,032, 1,102, 1,170-1,173, 1,246, 1,613 and 1,656-1,658 cm -1 ), explained by the development of inflammation and increased cell turnover.…”
Section: Discussionmentioning
confidence: 99%
“…The authors collected UC and HC tissue samples and examined the mucosal and serosal surfaces, achieving a classification sensitivity of 82% and a specificity of 89% from the mucosal surface and 87% sensitivity and 93% specificity from the serosal surface. 70 Their study indicated the possibility of real-time diagnosis with the ability to observe changes within UC colon tissue which are not apparent in histological examination. Spectral areas of interest revealed significant changes in peaks assigned as proteins, lipids and nucleic acids due to the increase in levels of inflammation.…”
Section: Ibd Diagnosis and Discriminationmentioning
confidence: 99%
“…demonstrating one of the first such applications. The authors collected UC and HC tissue samples and examined the mucosal and serosal surfaces, achieving a classification sensitivity of 82% and a specificity of 89% from the mucosal surface and 87% sensitivity and 93% specificity from the serosal surface 70 . Their study indicated the possibility of real‐time diagnosis with the ability to observe changes within UC colon tissue which are not apparent in histological examination.…”
Section: Applicationsmentioning
confidence: 99%
“…Pre-malignant stages of colorectal cancer can also benefit from the use of RS. Veenstra et al [ 15 ] evaluated the spectra of patients with ulcerative colitis, focusing on the mucosal and serosal regions. Regarding the mucosa, RS had a sensitivity of 82% and specificity of 89%.…”
Section: Colonmentioning
confidence: 99%
“…Regarding the mucosa, RS had a sensitivity of 82% and specificity of 89%. For the serosal regions, RS had a sensitivity of 87% and a specificity of 93% [ 15 ].…”
Section: Colonmentioning
confidence: 99%